When epidemics become narrative, women get bogged down in scripts? - Skórzyńska, Izabela (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2023)
In the article, I follow the fate of women - heroines of the pandemic non-fiction literature in Poland, in order to verify the thesis that when women's experiences, such as pandemics or epidemics, become narratives, they themselves get stuck in women's narrative scripts and their variants characteristic of a specific culture. Treating storytelling, in the vein of anthropologists, as a primarily cultural practice, I wonder whether and how the attribution and/or adoption of stories about their own experiences by the heroines of the pandemic and epidemic, enables them to transgress the boundaries of scripts harmful to them, not invalidating their agency, but loudly manifesting their own point of view, different from the one established in culture.